The Role of Faculties of Education in Increasing Sustainable Environmental Awareness of Society - KARATAŞ, Abdullah (European Journal of Sustainable Development, 2013)
Environmental problems show their negativeeffects globally today.Increasing pollutionand changing climatic conditions reveal thissituation clearly. Environmental problems,affecting the future of all living things, are connected with the incorrect relations betweenman and nature. People have become alienated from nature seeing it as an endless sourceand as a result nature has become a tool for achieving anthropocentric objectives. It canbe said that such an anthropocentric viewis the real cause of environmental problems,but human and nature harmony should be structured immediately because environmentalproblems have reached to serious position.Consequently, human being is a livingcreature and he needs healthy and reliable environment to live like all other creatures.Unless changing anthropocentric view of peopletowards nature, law and fines will also behelpless. At this point, education plays a very important mission. Because it is possible tochange people's behavior andperspectives positively through education. For the creationof awareness about the importance of protecting environment in society, faculties ofeducation as teacher traininginstitutions are of great importance. Teachers, preparinggenerations for future and so shaping the future of a society, receive their professionalqualification and requirements for becoming ateacher from faculties of education, soteacher candidates should be educated verywell. Teacher candidates from all disciplines,educated with environmental consciousness, willbe able to transfer this consciousness totheir students when they graduate. Generations,given the love of nature at an early age bytheir teachers, can be eco-friendly individuals in the future and shed light onenvironmental problems.This theoretical studyaims to put forward the role of faculties ofeducation in increasing sustainable environmental awareness of society